Cancer Status in Pediatric Population of Chittagong, Bangladesh - Aziz, Tasmiah Tahera; Hayee, Samira; Pulock, Orindom Shing; Haider, Maliha; Banu, Tahmina (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Cancer is increasing at an alarming rate worldwide and Bangladesh is no exception. The lack of data on cancer especially in the pediatric age group representing almost half the population of Bangladesh persuaded us to undertake this study. Methods: A cross-sectional study has been conducted in Chittagong Medical College & Hospital (CMCH); the only tertiary hospital in Chittagong and Chattagram Ma- O-Shishu Hospital (CMOSH); the largest private hospital in Chittagong. From 3rd July to 18th July, data on 704 diagnosed cancer patients were collected. Type of cancer in respect of age & sex and Socio-demographical profile was determined. Results:Out of 704 cancer patients, 74 (10.51%) were in pediatric age group. Male to Female ratio was 1.74:1. We found 1.35% (1) of the pediatric cancer patientswere infants whereas 40.54% (30) were children and 45.95% (34)were Adolescents. Leukemia is the commonest (47.29%) pediatric malignancy followed by lymphoma (16.2%) irrespective of sex. In female, Leukemia (59.52%) & ovarian cancer (14.29%) are the most common according to our study whereas in male, Lymphoma (34.38%) and leukemia (34.37%) were the most frequently diagnosed. 8.1% (6) of our study subjects had metastasized cancer. 17.57% (13) of the patients had family history of cancer. 63.51% of the cancer patients were from rural area and 36.49% from urban area. Other than Chittagong Metropolitan (31.08%) area, 21.62% of the patients came from Cox’s Bazar. 77.03% of the patients were in the income range <10,000 BDT (<119.25 USD). Conclusion: Most of the pediatric cancer patients came from rural areas and belonged to poor income families. Family history of cancer was found in thirteen cases. Irrespective of age and sex Leukemia was the commonest type of cancer. Our study provides a gross overview of pediatric cancer status in Chittagong. Further implementation of the study can help to address the research gap in pediatric cancer. Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):3-10